Difference between revisions of "Newton's Inequality"
Etmetalakret (talk | contribs) m |
Turtleman64 (talk | contribs) m (→Background) |
||
Line 1: | Line 1: | ||
== Background == | == Background == | ||
− | For <math> x_1, \ldots, x_n </math>, we define the [[symmetric sum]] <math>s_k </math> to be the coefficient of <math>t^{n-k} </math> in the polynomial <math> \prod_{i=1}^{n}(t+x_i) </math> (see [[ | + | For <math> x_1, \ldots, x_n </math>, we define the [[symmetric sum]] <math>s_k </math> to be the coefficient of <math>t^{n-k} </math> in the polynomial <math> \prod_{i=1}^{n}(t+x_i) </math> (see [[Vieta's sums]]). We define the ''symmetric average'' <math>d_k </math> to be <math> \textstyle s_k/{n \choose k} </math>. |
== Statement == | == Statement == |
Revision as of 03:04, 28 January 2023
Contents
Background
For , we define the symmetric sum
to be the coefficient of
in the polynomial
(see Vieta's sums). We define the symmetric average
to be
.
Statement
For non-negative and
,
,
with equality exactly when all the are equal.
Proof
Lemma.
For real , there exist real
with the same symmetric averages
.
Proof.
We consider the derivative of . The roots of
are
. Without loss of generality, we assume that the
increase as
increases. Now for any
,
must have a root between
and
by Rolle's theorem if
, and if
, then
is a root of
times, so it must be a root of
times. It follows that
must have
non-positive, real roots, i.e., for some non-negative reals
,
.
It follows that the symmetric sum for
is
, so the symmetric average
.
Thus to prove Newton's theorem, it is sufficient to prove
for any . Since this is a homogenous inequality, we may normalize it so that
. The inequality then becomes
.
Expanding the left side, we see that this is
.
But this is clearly equivalent to
,
which holds by the rearrangement inequality.
Proof: without calculus
We will proceed by induction on .
For , the inequality just reduces to AM-GM inequality.
Now suppose that for
some positive integer
the inequality holds.
Let ,
,
,
be non-negative numbers and
be the symmetric averages of them.
Let
be the symmetric averages of
,
,
.
Note that
.
By induction this completes the proof.